2014
DOI: 10.3928/01477447-20131219-10
|View full text |Cite
|
Sign up to set email alerts
|

Orthopedic Inpatients’ Ability to Accurately Reproduce Partial Weight Bearing Orders

Abstract: Partial weight bearing is often prescribed for patients with orthopedic injuries. Patients’ ability to accurately reproduce partial weight bearing orders is variable, and its impact on clinical outcomes is unknown. This observational study measured patients’ ability to reproduce partial weight bearing orders, factors influencing this, patients’ and physiotherapists’ ability to gauge partial weight bearing accuracy, and the effect of partial weight bearing accuracy on long-term clinical outcomes. Fifty-one orth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 20 publications
0
13
0
Order By: Relevance
“…Thus it could be possible that during training in the treadmill with 20 kg body weight partial loading might be higher than 20 kg. Several studies showed that the majority of patients could not reproduce accurately partial weight bearing and exceeded their target load with about 20 kg over target load [2224]. Hence we accepted a possible inaccuracy of the treadmill since it is known that patients cannot put partial weight bearing of 20 kg into practice.…”
Section: Discussionmentioning
confidence: 90%
“…Thus it could be possible that during training in the treadmill with 20 kg body weight partial loading might be higher than 20 kg. Several studies showed that the majority of patients could not reproduce accurately partial weight bearing and exceeded their target load with about 20 kg over target load [2224]. Hence we accepted a possible inaccuracy of the treadmill since it is known that patients cannot put partial weight bearing of 20 kg into practice.…”
Section: Discussionmentioning
confidence: 90%
“…However, these methods do not represent dynamic activities (e.g. walking) and are not accurate in training patients to comply with partial weight-bearing (PWB) instructions [59]. Previous research shows that it is difficult for patients to comply with WB instructions [1,5,7,913].…”
Section: Introductionmentioning
confidence: 99%
“…walking) and are not accurate in training patients to comply with partial weight-bearing (PWB) instructions [59]. Previous research shows that it is difficult for patients to comply with WB instructions [1,5,7,913]. Reasons for non-compliance include [1] the difficulty to judge the load placed on the lower-limb, and [2] the use of inadequate training methods to achieve controlled PWB [1,7,11,13].…”
Section: Introductionmentioning
confidence: 99%
“…However, these methods do not represent dynamic activities (e.g. walking) and are not accurate in training patients to comply with partial weight-bearing (PWB) instructions [5][6][7][8][9]. Previous research shows that it is difficult for patients to comply with WB instructions [1,5,7,[9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…walking) and are not accurate in training patients to comply with partial weight-bearing (PWB) instructions [5][6][7][8][9]. Previous research shows that it is difficult for patients to comply with WB instructions [1,5,7,[9][10][11][12][13]. Reasons for non-compliance include [1] the difficulty to judge the load placed on the lower-limb, and [2] the use of inadequate training methods to achieve controlled PWB [1,7,11,13].…”
Section: Introductionmentioning
confidence: 99%